Penentuan Rute Distribusi Barang ke Toko Menggunakan Metode Saving Matrix dan Algoritma Nearest Neighbor - Dyah Calystha Rahma; Tribowo Rachmat Fauzan (Jurnal Sekretaris dan Administrasi Bisnis, 2025)
PT XYZ is a company engaged in retail with more than 19 thousand stores, a number that continues to grow every month. One of the problems faced is the lack of efficiency in the process of distributing goods from distribution centers to stores. This inefficiency occurs due to new stores being added to the delivery route without optimal planning, resulting in wasted mileage and increased fuel costs. A combination of Saving Matrix and Nearest Neighbor methods is used to determine a more optimal distribution route. The Saving Matrix method helps combine routes efficiently by considering vehicle capacity, while Nearest Neighbor helps arrange the order of deliveries based on the shortest distance within the route group. This research succeeded in producing more efficient distribution routes. The number of distribution routes was successfully reduced from the initial total distance of 112.8 km to 90.6 km. In addition, there are savings in distribution costs, from Rp 6,808,200 to Rp 5,883,900. By applying the Saving Matrix and Nearest Neighbor methods, PT XYZ was able to save distance by 19.4% and reduce total shipping costs by 13.5%.